2006
DOI: 10.1002/mop.21699
|View full text |Cite
|
Sign up to set email alerts
|

User's hand effects on EMC internal GSM/DCS dual-band mobile phone antenna

Abstract: User's hand effects on an electromagnetic‐compatible (EMC) internal dual‐band mobile phone antenna for GSM/DCS operation are studied. The EMC internal antenna can be placed in direct contact with nearby conducting elements, without degradation in the antenna performances. Experimental and simulation studies are conducted to analyze the user's hand effects on this EMC antenna. Obtained results indicate that the user's hand affects not only the impedance matching of the antenna, but also the radiation characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…In this case, as the user's hand is considered as a very lossy material [14][15][16][17][18][19][20][21], its effects on the radiation efficiency and radiation patterns of the proposed antenna will be interesting and also important for practical applications. Results obtained from the simulation model with the phantom hand provided by SPEAG SEMCAD [22] are analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, as the user's hand is considered as a very lossy material [14][15][16][17][18][19][20][21], its effects on the radiation efficiency and radiation patterns of the proposed antenna will be interesting and also important for practical applications. Results obtained from the simulation model with the phantom hand provided by SPEAG SEMCAD [22] are analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the bones occupying most volume of the user's hand, the equivalent parameters of the one-layer simulation hand model including the forearm in this study are selected to be close to those of the bones. With comparison to the multilayer simulation hand model [6], the use of the one-layer equivalent hand model can greatly reduce the simulation time [7]. This makes it possible for obtaining an efficient and reliable simulation study for the mobile antenna with the presence of the user's hand.…”
Section: Simulation Hand Model and Studied Planar Dtv Antennamentioning
confidence: 99%
“…This makes it necessary to include the user's hands in the study of the antenna performances, since it has been concluded that the user's hands function as an effective lossy medium and will affect the antenna performances significantly [6,7]. For this consideration, we present in this article the study of the planar DTV antenna in the PMP with the presence of the user's hands.…”
Section: Introductionmentioning
confidence: 97%
“…However, in practice, the handset antenna performance is strongly affected by other important factors such as hand interaction [23][24][25] and human head effect [26][27][28][29][30][31][32][33][34][35][36][37]. The user significantly interacts with the radiating system, especially during a phone call, affecting its performance and causing radiation losses as well as detuning effects.…”
Section: Introductionmentioning
confidence: 99%